EVALUATION OF A FOOT SELF-CARE BOOKLET FOR DISCHARGE PLANNING AMONG PATIENTS WITH DIABETES MILLITUS - Widyarani, Linda; Rahayu, Novi Widyastuti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2026)
Introduction: Effective discharge planning is essential to ensure continuity of care and improve patient outcomes, particularly among individuals with diabetes mellitus who are at high risk of foot complications. Nurses play a critical role in delivering discharge education; however, conventional approaches are often limited in supporting patient understanding and self-management. The use of structured educational media, such as booklets, may enhance patient knowledge and promote independent foot self-care.Objective: This study aimed to evaluate the effect of a foot self-care booklet, integrated into the discharge planning process, on the knowledge of patients with diabetes mellitus.Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 39 patients with diabetes mellitus at RSUD Wonosari between June and August 2023. Participants were selected using total sampling. Knowledge of foot self-care was measured using a structured questionnaire before and after the intervention. The intervention consisted of health education using a foot self-care booklet delivered during discharge planning. Data were analyzed using the paired t-test, with a significance level set at p < .05.Results: The mean pretest score was 63.90 (SD = 7.76), while the mean posttest score increased to 88.00 (SD = 4.40). Statistical analysis showed a significant improvement in knowledge following the intervention (p < .001), indicating the effectiveness of the booklet-based education.Conclusion: The integration of a foot self-care booklet into discharge planning significantly improves patients’ knowledge of foot self-care. This educational approach can be adopted as a practical and effective strategy to support self-management and reduce the risk of diabetic foot complications.